A review of resource curse burden on inflation in Venezuela. (1st August 2020) - Su, Chi-Wei; Khan, Khalid; Tao, Ran; Umar, Muhammad
Abstract: This study reviews whether oil prices (OP) in Venezuela affect inflation (INF) in the presence of geopolitical risk (GPR). The country is exceedingly dependent on oil results in geopolitical destabilization and extremely exposed to OP shocks that contribute to higher inflation. The empirical results find comovement between OP and INF in short to medium run. However, GPR explains OP in the mid-term and its effect transmit to INF in the short run. Moreover, the correlation between OP and INF is identified in the long run and more evident in the presence of GPR, suggests that OP plays a crucial role in the formation of INF in the context of higher uncertainties. The findings are in line with the aggregate model, explains that GPR is a leading factor of OP which can be reflected in INF. Venezuela is highly dependent on oil because of the "Resource Curse" and extremely exposed to OP shocks that contribute to higher inflation which can be curtailed through diversification. Further, GPR stability in Venezuela is decidedly essential for the growth of the economy and low inflation. The institutional reforms reinforced by the legal regulatory system can provide support to the government system and enhance the immunity against external shocks as well as efficiency. The backing financial institutions to the currency will restore the consumer and business confidence in the economy which can help control the higher inflation. Highlights: Review whether oil prices (OP) in Venezuela affect inflation (INF) in the presence of geopolitical risk (GPR). Geopolitical destabilization and extremely exposed to OP shocks that contribute to higher inflation. OP plays a crucial role in the formation of INF in the context of higher uncertainties. The findings in line with the aggregate model and GPR is a leading factor of OP can be reflected in INF. Venezuela is highly dependent on oil because of the "Resource Curse".